Advocates As Law Enforcers: Duties And Functions Of Legal Powers In The Religious Court System Based On Law No. 18 Of 2003 - Restu Annisa Ilma; Abdul Halim Nasution; Dwi Cahyani; Winda Pricilia; Fanny Azelita Humairah; Silvani Febrian; Ahsanul Rizki (Jurnal Multidisiplin Sahombu, 2025)
Advocate in The laws in Indonesia, in particular according to Constitution Number 18 of 2003 concerning Advocate, is profession enforcer free, independent and responsible law answer in to uphold Law. Advocate own rights, obligations and responsibilities answer in accordance with rule applicable law. As profession that plays a role important in enforcement justice, advocate own not quite enough answer big in guard certainty law, especially in religious courts that often handle matters of a nature personal and religious. Research This use method law normative with approach analysis qualitative. Data obtained from regulation legislation, literature law, and studies relevant cases about role advocate in religious courts. Findings study This disclose that advocate own position important in protect rights client, provide defense fair law, and support smooth running of the religious court process in accordance with with principle justice and provisions applicable law. Advocate No only functioning as advisor law, but also as bodyguard integrity system religious courts with give contribution to justice substantial, especially in case related law family and legacy in context of Islam. Research this also suggests the need Updates regulation For increase role advocate in religious courts.